Curved approach in high jump induces greater jumping height without greater joint kinetic exertions than straight approach - Sado, N.; Yoshioka, S.; Fukashiro, S. (Medicine & Science in Sports & Exercise, 2022)
Purpose: The most height-specific jumping mode, the athletic high jump, is characterized as a running single-leg jump (RSLJ) from a curved approach. The main advantage of a curved approach is believed to be facilitation of bar clearance. However, the effect of a curved approach on center-of-mass (CoM) height generation has not been clarified. Here, we show that the curved RSLJ (C-RSLJ) is more suitable than the straight RSLJ (S-RSLJ) for CoM height generation. Methods: We collected data using motion capture from 13 male high jumpers (personal best, 2.02-2.31 m) that performed C-RSLJ and S-RSLJ. We then compared the energy generation contributing to CoM height (Evert) in each approach. Results: All participants attained greater CoM height in C-RSLJ than in S-RSLJ (difference, 0.055 ± 0.024 m). Three-dimensional joint kinematics and kinetics were similar between both approaches, except for the ankle plantar-flexion torque, which was smaller in C-RSLJ. The sum of positive work was comparable between the approaches, whereas the sum of negative work in C-RSLJ was significantly smaller than in S-RSLJ. The shank forward rotation induced a larger difference in Evert generation between C-RSLJ and S-RSLJ (0.80 ± 0.36 J/kg) than any other segment (=0.36 J/kg). Conclusions: Compared with a straight approach, a curved approach induces greater CoM height without increasing joint kinetic exertions during takeoff. The curved approach changes the initial condition of the takeoff and promotes the transformation of horizontal kinetic energy into Evert. This study provides novel practical perspectives for high jumpers and highlights the importance of segment biomechanics in human motor performance.